Measuring vocal fatigue in sports coaches - Yanushevskaya, Irena (My University, 2017)
Objective: This study explores the immediate impact of prolonged voice use by professional sports coaches. Method: Speech samples including sustained phonation of vowel /a/ and a short read passage were collected from two professional sports coaches. The audio recordings were made within an hour before and after a coaching session, over three sessions. Perceptual evaluation of voice quality was done using the GRBAS scale. The speech samples were subsequently analyzed using Praat. The acoustic measures included fundamental frequency (f0), jitter, shimmer, Harmonics-to-Noise ratio and Cepstral Peak Prominence. Main results:The results of perceptual and acoustic analysis suggest a slight shift towards a tenser phonation post-coaching session, which is a likely consequence of laryngeal muscle adaptation to prolonged voice use. This tendency was similar in sustained vowels and connected speech. Conclusion: Acoustic measures used in this study can be useful to capture the voice change post-coaching session. It is desirable, however, that more sophisticated and robust and at the same time intuitive and easy-to-use tools for voice assessment and monitoring be made available to clinicians and professional voice users.
PUBLISHED
Keywords: Vocal fatigue; Sports coaches; f0; Jitter; Shimmer; HNR; Cepstral Peak Prominence; Acoustic analysis